2013
DOI: 10.1074/jbc.m113.456046
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Nox4 to a Plasma Membrane Scaffold Is Required for Localized Reactive Oxygen Species Generation and Sustained Src Activation in Response to Insulin-like Growth Factor-I

Abstract: Background: Nox4-derived ROS is required for Src oxidation and activation. Results: Grb2 recruits Nox4 to the scaffold protein SHPS-1, and Nox4 colocalization with Src on SHPS-1 allows Nox4 to activate Src. Conclusion: Nox4 recruitment to SHPS-1 is essential for sustained Src activation and cell proliferation. Significance: This is the first report that localized ROS generation mediates growth factor signaling in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 34 publications
4
50
0
Order By: Relevance
“…ROS can also oxidize cysteine residues of Src, which directly leads to SFK activation. The activation of Src by oxidation is considered to be maintained longer(for at least 3 h)than the activation by phosphorylation (20). In this study, the activity of SFK was sustained for 2 h and the result was consistent with the previous reports.…”
Section: Effect Of Dpi On the P38 Mapk Activity And Expression Of Clasupporting
confidence: 82%
“…ROS can also oxidize cysteine residues of Src, which directly leads to SFK activation. The activation of Src by oxidation is considered to be maintained longer(for at least 3 h)than the activation by phosphorylation (20). In this study, the activity of SFK was sustained for 2 h and the result was consistent with the previous reports.…”
Section: Effect Of Dpi On the P38 Mapk Activity And Expression Of Clasupporting
confidence: 82%
“…Src is activated by Nox4-derived ROS elevation to mediate subsequent downstream signaling [22]. In this study, we observed that the phosphorylation of SrcY419 in endothelial cells was increased in a time-dependent manner after 100 mg/L AGEs treatment (Fig.…”
Section: Resultssupporting
confidence: 48%
“…Another study and our present data revealed recruitment of Nox4 to the membrane and subsequent Src activation evoked by the translocation [22]. Moreover, inhibition of oxidative stress attenuated AGE-induced Src phosphorylation.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…By acting as both mutagens and mitogens, ROS is capable of inducing oncogenic transformation and promoting carcinogenesis and is proposed to play major roles in tumor cell transformation, progression, and metastasis (10). Growth factor and mitogenic signals that promote cancer cell growth and survival have been linked to altered mitochondrial functions and generation of ROS (11)(12)(13)(14)(15)(16). However, the molecular mechanism of whether and how the aberrant growth factor/mitogenic signals in tumor cells may control mitochondrial mass and respiration still remains unclear.…”
mentioning
confidence: 99%